ANALISIS PENGARUH AKSI BELI-JUAL ASING, KURS, DAN INDEKS HANG SENG TERHADAP INDEKS HARGA SAHAM GABUNGAN DI BURSA EFEK INDONESIA DENGAN MODEL GARCH - Budi Frensidy (Universitas Trisakti, 2008)
The identify of investors doing a transaction, either domestic or foreign, is so transparent in our capital market. This allow some traders to follow the trading of a certain group of traders, namely foreign investors. This herding behavior is based on two assumptions. First, foreign investors are believed to have bigger capital. Second, they are also regarded to own more superior information and better fundamental outlook than the domestic investors.Based on this phenomenon, it is predicted that there is a positive relationship between IHSG (the composite stock index of Indonesian Stock Exchange) and the net daily foreign fund flow in the market. Besides confirming the above hypothesis, this study also tries to find out the effect of exchange rate and regional stock index on the IHSG, using GARCH model.Keywords: Foreign investor, Herding, Exchange rate